2021
DOI: 10.3390/en14217408
|View full text |Cite
|
Sign up to set email alerts
|

Energy and Environmental Effects of Human Habits in Residential Buildings Due to COVID-19 Outbreak Scenarios in a Dwelling near Rome

Abstract: The COVID-19 pandemic and resulting containment measures have shown that energy consumption in buildings is linked to several factors, such as living habits, occupancy profiles, and heating ventilation and air conditioning (HVAC) systems. This paper addresses the influences of such factors on energy consumption in a residential building, analysing different scenarios (pre-COVID-19, lockdown, post-COVID-19), in terms of discomfort and energy needs, through the new hourly calculation method (UNI EN ISO 52016). E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The issue of overestimation could be overcome using a tailored approach that assumes more realistic profiles for representing users' behavior and the functioning of plant systems and equipment. Many studies consider occupant behavior as an influential factor for the uncertainty of energy building performance [17] further remarked upon after the COVID-19 pandemic [18]. According to Gram-Hassend and Georg [19] the occupants' behavior in the different types of residential buildings affects energy consumption, depending also on the building characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…The issue of overestimation could be overcome using a tailored approach that assumes more realistic profiles for representing users' behavior and the functioning of plant systems and equipment. Many studies consider occupant behavior as an influential factor for the uncertainty of energy building performance [17] further remarked upon after the COVID-19 pandemic [18]. According to Gram-Hassend and Georg [19] the occupants' behavior in the different types of residential buildings affects energy consumption, depending also on the building characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Snow et al attempted to clarify changes in living behavior through detailed power consumption of each branch circuit of 17 households in Brisbane, Australia, meter-level data analysis of 400 households, and in-depth interviews with the residents of 17 households [11] . Palladino et al simulated the impact on residential power consumption assuming that social events such as city lockdown occurred in a residential area near Rome, Italy, in summer, winter, and mid-season [12] . Chen et al focused on the impact of the increase in household power consumption and the shift in power demand by time of day on power charges during the pandemic and conducted an interview survey of 632 people in the state of New York, USA, and analyzed their intention to introduce Home Energy Management Systems (HEMS) to pay US$5/month for energy management [13] .…”
Section: Introductionmentioning
confidence: 99%
“…A combined energy-economic assessment of the airtightness was proposed in [12], demonstrating that the reduction in the infiltration rate through the external building envelope, glazing, and doors is both a valuable refurbishing path and a cost-effective measure. Concerning the actual presence of people in buildings, a study on Italian dwellings demonstrated that the higher the occupancy (e.g., homemakers), the lower the energy demand for space heating [13]. For non-residential buildings, occupancy monitoring is strongly recommended to enhance the energy saving due to the customization of heating, ventilation, and air conditioning (HVAC) and lighting operation [14].…”
Section: Introductionmentioning
confidence: 99%